A comparison between monocanalicular and pushed monocanalicular silicone intubation in the treatment of congenital nasolacrimal duct obstruction - Dima Andalib (International Journal of Ophthalmology, 2014)
AIM: To compare the success rate of monocanalicular versus pushed monocanalicular silicone intubation (PMCI) of the nasolacrimal duct for congenital nasolacrimal duct obstruction (CNLDO).METHODS: In a prospective randomized clinical trial 53 eyes of 49 patients with CNLDO underwent either monocanalicular silicone intubation (MCI) (n=28 eyes) or PMCI (n=25 eyes). All procedures were performed by 1 oculoplastic surgeon. Treatment success was defined as the complete resolution of epiphora at 3mo after tube removal.Results: The surgical outcome was assessed in 20 eyes with MCI and 20 eyes with PMCI. The mean age of treatment was 26.25±10.08mo (range, 13-49mo) for MCI and 26.85±12.25mo (range, 16-68mo) for PMCI. Treatment success was achieved in 18 of 20 eyes (90.0%) in the MCI group compared with 10 of 20 eyes (50%) in the PMCI group (P=0.01). In the PMCI group, the tube loss (30%) was greater than the MCI group (5%), however the differences between the 2 groups proved to be not significant (P=0.91).CONCLUSION: Our results indicate that MCI has higher success rate in CNLDO treatment compared with PMCI in this small series of patients.